THEORETICAL FOUNDATIONS OF PROFESSIONAL DEFORMATION PREVENTION IN FUTURE TEACHERS (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This thesis highlights the cases of potential professional deformation in the activities of future teachers and the necessity of its prevention. The theoretical and pedagogical foundations of professional deformation are analyzed, and the importance of developing preventive mechanisms is substantiated. Furthermore, foreign and local studies are compared, and effective approaches are presented.